Family influence on antisocial behavior in adolescents from Arequipa, Peru - Rivera, Renzo (2016)
The aim was to determine the influence of the family on antisocial behavior in non-institutionalized adolescents. The sample consisted of 929 high school students, between 14 and 17 years old. In the process, a battery of test about social-demographic data, antisocial behavior and family functioning: relationship, satisfaction, cohesion, adaptability and family communication was applied. We analyzed variables using structural equation models differentiated by sex. The results indicated that family functioning in both sexes and the number of siblings in males are considerable factors when discussing antisocial behavior. The risk factors are: child abuse and violence between parents in females, besides consumption of alcohol by parents in both sexes.